A study of linguistic features of proverbs containing words denoting plants in english versus vietnamese - Nguyễn,Thị Minh Phượng. (2016)
Proverb is an indispensable part of language which is assumed to reflect the cultural values and beliefs of a nation. Proverbs in general and proverbs containing words denoting plants in particular are of culture-specific nature and vary from culture to culture. On this basis, the thesis investigates the similarities and differences of proverbs containing words denoting plants in English and Vietnamese in terms of semantic features, rhetorical devices and syntactic features. The thesis is carried out and based on descriptive and contrastive methods, 300 samples in English and Vietnamese were taken from different sources such as dictionaries, books, the Internet … for the sake of semantic features, rhetorical devices and syntactic analysis. The thesis also suggests some implications for the teaching and learning of proverbs in general, and those for the translating of proverbs containing words denoting plants from English to Vietnamese and vice versus in particular.